Microsomal Transfer Protein Inhibitors, New Approach for Treatment of Familial Hypercholesterolemia, Review of the Literature, Original Findings, and Clinical Significance. Issue 2 (April 2015) - Kolovou, Genovefa; Vasiliadis, Ioannis; Gontoras, Nikos; Kolovou, Vana; Hatzigeorgiou, Georgios
Summary: The genetic causes of cholesterol metabolism disorders usually lead to premature atherosclerosis. The most well recognized genetically caused hypercholesterolemia is familial hypercholesterolemia. Although the disease is well known, as the discovery of low‐density lipoprotein receptor, the classical treatment with lipid‐lowering drugs (statins, fibrates, ezetimibe, colesevelam) is still not adequate and new options are seeking. This review is an attempt to analyze the microsomal transfer protein (MTP) inhibitors as a new approach for treatment of familial hypercholesterolemia, to reviews the literature according to MTP inhibitors and finally to provide original findings.